Ferroic Functional Materials Experiment, Modeling and Simulation - Schröder, Jörg; C. Lupascu, Doru (CISM International Centre for Mechanical Sciences, Courses and Lectures, 2018)
The book covers experiments and theory in the fields of ferroelectrics, ferromagnets, ferroelastics, and multiferroics. Topics include experimental preparation and characterization of magnetoelectric multiferroics, the modeling of ferroelectric and ferromagnetic materials, the formation of ferroic microstructures and their continuum-mechanical modeling, computational homogenization, and the algorithmic treatment in the framework of numerical solution strategies.